Mining Industrialization and Deagrarianization in Rural Community (A case Study of Community Embalut and Bangunrejo, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan) - Gandi, Rajib; Sunito, Satyawan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
East Kalimantan province has issued a mining license (IUP) reached 1,192 pieces, until August 2014. Kutai Kartanegara is a county that issued the largest IUP is 407 companies, which 218 companies have been involved in the production, while the remaining 189 are still in the exploratory stage. Embalut village and village Bangunrejo which become part of the administration Tenggarong Seberang Sub-District, Kutai Kartanegara, is a village that has more than 30 years was associated with the mining industry, PT. Kitadin. The results showed that: (1) the mining industrialization has changed the structure of land in the village Embalut and village Bangunrejo where land holdings in both villages have concentrated on coal mining companies. (2) mining Industrialization increasingly encourage people to work or livelihood in outside agriculture (deagrarianization). This study used qualitative methods, with in-depth interview techniques, group discussions, observation, and study of literature / documents. Keywords: Industrialization Mining, deagrarianization, land tenure